DIGITAL STORYTELLING AND FORMATIVE MEDIATION IN CONTEMPORARY EDUCATIONAL SCENARIOS - Pereira Nicácio, Jailton; Trajano de Souza, Joseilson; Trajano de Souza, Josenete; Lisboa Galvão do Nascimento, Jonatha; Modesto Favacho, Kelsin; Helena de Paula Modesto Favacho, Lucia; Santos do Nascimento, Marielza; Campos Rodrigues, Mayara; Ricardo Pereira Accioly, Sérgio (Revista Gênero e Interdisciplinaridade, 2026)
Storytelling has gained relevance in the educational field by articulating narrative heritages with digital languages, fostering experiences that transcend traditional teaching. It doesn’t simply spark interest, but also acts as a formative mediation, connecting school knowledge to life repertoires. This combination fosters student authorship, expands critical interpretation, and enables the construction of more open and collaborative learning. On the other hand, the incorporation of digital narratives highlights its limits. Stimulus overload can reduce concentration, and the use of images and sounds sparks ethical discussions about cultural property, data exposure, and forms of representation. These factors indicate that storytelling needs to be considered as an intentional pedagogical practice, oriented toward sustaining consistent formative bonds rather than being limited to aesthetics. The research proposal was developed with the goal of understanding how storytelling, when combined with digital technologies, can foster innovative practices while simultaneously addressing ethical dilemmas. The methodology used consisted of critical bibliographical research, supported by national and international works that discuss narratives, education, and technology in dialogue. The analytical process sought to compare diverse readings, map contradictions, and construct authorial interpretations capable of illuminating the place of storytelling in contemporary education.